Transient gestational hypertension and pre-eclampsia: Two case reports and literature review on the need for stringent monitoring - Nnabuike C. Ngene; Ghadah Daef (South African Family Practice)
Transient gestation hypertension is a contributor to adverse pregnancy outcomes particularly when it progresses to pre-eclampsia (PE). This requires frequent monitoring. We illustrate the need for stringent monitoring of gestational hypertension, transient gestational hypertension (TGH) and PE without severe features and conducted a brief rapid review of the literature. Two cases are presented: Firstly, a 25-year-old primigravida at 30 gestational weeks who had an isolated TGH with high blood pressure (BP) of 141/87 mmHg, which was not investigated. Four weeks later, she presented with a BP of 202/128 mmHg, imminent eclampsia and intrauterine foetal death and had an uncomplicated induction of labour and delivered a 1400 g macerated male stillborn. Secondly, a 30-year-old primigravida at 30 gestational weeks who developed PE but her monitoring was compromised initially by inadequate healthcare capacity including unavailability of hospital bed-space for inpatient care and later by poor clinic attendance as a result of poor finances. At 32 gestational weeks, she presented with decreased foetal movement and was diagnosed as haemolysis, elevated liver enzymes, low platelet count (HELLP) syndrome and intrauterine foetal death. She was stabilised, had induction of labour and delivered a 1400 g male macerated stillborn. Thereafter, the need for her to go home to complete the cultural burial rites of her baby and the pressure from her workplace resulted in an inadequate postpartum follow-up care. In conclusion, transient gestational hypertension is associated with adverse maternal and foetal outcomes, including foetal demise. Unavailability of hospital bed-space and poor personal finances interfere with stringent monitoring of hypertensive disorders and can be associated with adverse pregnancy outcomes. Stringent laboratory monitoring in these cases is defined by the authors as testing at least blood levels of serum Creatinine, Haemoglobin concentration, Alanine transaminase and Platelet count (abbreviated as ‘CHAP’) weekly.